Evaluating micas in petrologic and metallogenic aspect: Part II—Applications using the computer program Mica+ - Yavuz, Fuat (Elsevier BV, 2003)
Abstract The significance of micas for metallogenic and petrologic studies results from their widespread occurrence in magmatic, metamorphic, and hydrothermal ore-related rocks. For example, the mineral chemistry of biotites, and especially their halogen content, may provide an important guide in understanding the composition and circulation of fluids during or later emplacement of magmatic rocks and associated with hydrothermal mineralization. The Mica + program has been developed to evaluate mica composition both from magmatic rocks and associated with porphyry copper and Mo–Au–Sn–W–Be systems. The validity of the Mica + program has been tested for variety mica data sets selected from literature. The concept of computer program can be grouped into three major topics, respectively: (i) mica classification and discrimination; (ii); estimation of intensive parameters; and (iii) halogen contents as an indication of hydrothermal ore deposits. Halogen systematics and intensive thermodynamic parameters (i.e., T , f O 2 , f H 2 O) of micas both from porphyry Cu–Au–Mo mineralization system and magmatic rocks were estimated using the Mica + program. Program output was compared with the original published results. Evaluation suggests that the Mica + can be used efficiently in studying the mica composition in respect to petrologic and metallogenic aspects.